Reporting of placebo medication descriptors in randomised controlled trials: A review of three medical journals. Issue 1 (September 2020) - Watson, Michelle; Arundel, Catherine; Clark, Laura; Cook, Liz; Sbizzera, Illary
Clinical trials involving a placebo enable researchers to determine the effectiveness of a product; however, ensuring a placebo matches an active treatment takes great consideration, time and costs. We aimed to assess the reporting quality of blinding descriptions for placebo medication treatments and consider this in relation to funding support (commercial or non-commercial). The Journal of the American Medical Association (JAMA); the Lancet and the New England Journal of Medicine (NEJM) were searched for randomised clinical trials, and 117 papers involving a placebo medication, published between 1 April 2016 and 31 March 2017, were extracted. The data were analysed for the number of publications reporting characteristics of placebo treatments, frequency of the characteristics and source of funding. Three quarters of the articles reported at least one characteristic of the placebo. The Lancet and JAMA consistently had this information present; however, this was observed less in the NEJM. The most common characteristic was 'matching placebo', followed by contents of the placebo, packaging and appearance. Texture, taste and smell were least reported. Within those supported by commercial funding, two-thirds reported at least one characteristic of the placebo treatment, whilst almost all of the articles without commercial funding reported at least one characteristic. Efforts are being made to include descriptions of blinded medication; however, inconsistencies suggest that guidelines are not always being followed, and more can be done to improve reporting. Future research should focus on the reasons for inadequate recording and aim to reduce the inconsistencies observed.